2015
DOI: 10.1007/s10649-015-9599-x
|View full text |Cite|
|
Sign up to set email alerts
|

The role of theory building in the teaching of secondary geometry

Abstract: Although mathematical practice has traditionally valued two distinct kinds of mathematical work-referred to by Gowers (2000) as theory building and problem solving-activity in classrooms appears to be organized largely around the latter, rather than the former. This study takes up the question of whether there is a customary role for theory building in the secondary geometry course and to what extent teachers of geometry hold students accountable for that disposition. We analyze records from study groups compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…This shows that the PSMTs need not only an understanding of what counts as valid argument, but also an adequate knowledge of choosing accepted definitions, axioms, and facts. Various properties and postulates that underlie in an argument made in the proof are usually not spelled out, but rather are assumed to have been already learned and internalized by students (Schleppegrell, 2007;Weiss & Herbst, 2015). Therefore, it might not be surprising to see students have difficulties interpreting or using theorems on their own.…”
Section: Verifying Presented Statements and Constructing A Justificationmentioning
confidence: 99%
See 1 more Smart Citation
“…This shows that the PSMTs need not only an understanding of what counts as valid argument, but also an adequate knowledge of choosing accepted definitions, axioms, and facts. Various properties and postulates that underlie in an argument made in the proof are usually not spelled out, but rather are assumed to have been already learned and internalized by students (Schleppegrell, 2007;Weiss & Herbst, 2015). Therefore, it might not be surprising to see students have difficulties interpreting or using theorems on their own.…”
Section: Verifying Presented Statements and Constructing A Justificationmentioning
confidence: 99%
“…Research has demonstrated that various properties and postulates that underlie in an argument made in the proof are not spelled out, but rather are assumed to have been already learned and internalized by students (Schleppegrell, 2007;Weiss & Herbst, 2015). As a result, students have difficulties interpreting, or using theorems on their own (Zeybek Simsek, 2020).…”
Section: Implications Of the Studymentioning
confidence: 99%